Yield, Reproductive Efficiency and Quality of Groundnut as Influenced by Water Stress at Different Growth Stages - Garana, B B; Yadav, B S (Annals of Arid Zone, 2016)
Groundnut was subjected to water stress during flowering, pegging, pod formation and pod development stages corresponding to 23-47, 33-55, 57-79 and 73-95 DAS at individual, any two and three growth stages alongwith control of no water stress. Water stress to the crop significantly reduced dry matter yield, number of flowers, total and effective pegs, pod : peg ratio, pod : haulm yield ratio, pod yield and shelling percentage. These parameters decreased with increase in the cycle/period of water stress. The magnitude of reduction in pod yield due to single, double and triple cycle of water stress over that of unstressed plants was 48.2, 58.1 and 69.7%, respectively. Pod development stage along or in combination with any other stage (s) with water stress was found most sensitive for pod yield, reproductive efficiency and shelling percentage whereas pegging stage alone or in combination with any other stage (s) was sensitive to haulm yield.